Pentingnya Standardisasi Big Data dalam Official Statistics - Nugraha Wahyu Putra Supiadi (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Big data is characterized by large data volumes, complex variations, and has great potential to improve the production and dissemination of official statistics by national statistical organizations (NSOs). However, the use of big data as a source of official statistics also has challenges, especially in terms of data quality, access, and standards. Therefore, the standardization of big data in official statistics is very important. The unavailability of big data standardization is an obstacle in its use for official statistics. The importance of standardizing big data in official statistics refers to improving efficiency, quality, and credibility in the production of official statistics, as well as the ability to integrate big data with other data sources.